Solar Cells: A Depletion‐Free, Ionic, Self‐Assembled Recombination Layer for Tandem Polymer Solar Cells (Adv. Energy Mater. 5/2014). Issue 5 (April 2014) - Lee, Jinho; Kang, Hongkyu; Kong, Jaemin; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> In article number 1301226, Kwanghee Lee and co‐workers report an innovative method by which to achieve depletion‐free recombination layers composed of poly(3, 4‐ethylenedioxythiophene): poly(styrenesulfonate (PEDOT:PSS) and a nonconjugated polyelectrolyte via ionic self‐assembly. These recombination layers form tunnel junctions with different work functions on each of their surfaces. The tandem solar cells incorporating these recombination layers are reported to exhibit solar power conversion efficiencies of greater than 8.3%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>